Bridging the Analog-Digital divide: critical literacies and procedural design in young people's game-making practices. (3rd April 2021) - Gee, Elisabeth R.; Aguilera, Earl
ABSTRACT: Over the past several decades, the concept of critical literacy has been applied to an increasing range of multimodal texts mediated by digital technologies. Expressive forms such as fan-fiction, digital storytelling, and gaming have presented unique opportunities forunderstanding critical literacy practices. Within the more specific field of game studies, a growing body of scholarship demonstrates how issues of ideology, politics, and power are woven into and expressed through the medium of games – whether digital or analog. This paper builds on this tradition by offering a critical analysis of a semiotic resource that digital and analog games share – the designed processes that shape experiences of meaning-making through acts of play. Examining data from a study of teens' participation in a library-based board game-making workshop, this paper highlights the ways participants engaged in critical literacy practices when asked to address a social issue through game design. The paper draws on techniques of discourse analysis to demonstrate how participants engaged with ideological dimensions of procedural literacy through design-centered discourse. Findings suggest that viewing game-making through the lens of procedurality can be a generative way to explore critical literacy practices in relation to contemporary social issues.